Strength in Numbers. A Short Note on the Past, Present and Future of Large Historical Databases - Lionel Kesztenbaum (Historical Life Course Studies)
Historical demography is inherently associated with constructing large-scale databases from historical records. Although there have been tremendous changes in the way they are constructed, many of the challenges remain. Throughout his career, Kees Mandemakers has been instrumental in facing some of these challenges, particularly those related to the conservation, standardization, and dissemination of databases. This short contribution discusses the evolution of large historical databases in historical demography.